American black bears perceive the risks of crossing roads. (23rd March 2018) - Ditmer, Mark A; Rettler, Spencer J; Fieberg, John R; Iaizzo, Paul A; Laske, Timothy G; Noyce, Karen V; Garshelis, David L
Abstract : When black bears cross roads, their HRs increase, indicating heightened alertness to danger. Wildlife reacts to roads in various ways, but it is unknown whether road crossings are stressful. We monitored black bears with cardiac monitors and GPS-collars in Minnesota. On average, bears crossed a road once a day; their HRs increased when 100 m away, and increased more with higher traffic volume, but not enough to suggest roadway interactions were highly stressful. Abstract: Roadways may negatively impact wildlife species through vehicular-related mortality and spatial displacement or obstruction. Here, we investigated physiological responses, which provide insights into the animal's perception of its environment. We deployed Global Positioning System (GPS)-collars in combination with cardiac biologgers on American black bears ( Ursus americanus ; 18 bear-years) in areas with differing road densities across Minnesota, USA. We tested whether bears exhibited acute stress responses, as defined by significant increases in heart rate (HR), associated with road crossings. Maximum HR between successive telemetry locations were, on average, 13 bpm higher when bears were known to cross a road. They crossed a road, on average, once per day. Different demographic groups (males, females with and without cubs) responded similarly. We found stronger HR responses when crossing high-traffic roads relative to low-traffic in half of the bear-year combinations we sampled. Bears crossed high-traffic roads mainly at night, but low traffic roads during daylight. Bear HRs first became elevated when 73−183 m away from roadways. Our findings suggest that roadways act as an acute stressor, but the magnitude of the stress response appears to be mild. Elevated HRs may reflect an increased vigilance and recognition of threat when preparing to cross a road. Bears' recognition and alertness to human-related threats is adaptive for living in human-altered landscapes.